Laparoscopic splenectomy using bipolar vessel sealing system - Jassim, Aws Kh.; Turkey, Fareed A.; Ibraheem, Ahmed A. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Newly developed vessels sealing device built upon bipolar diathermy technology had a great impact on facilitating advances laparoscopic surgery. Laparoscopic splenectomy is well established procedure but in this study the procedure is totally based on bipolar vessel sealing system in devascularization of the spleen. Objective: To evaluate the safety of laparoscopic splenectomy with vessels sealing device and its outcome. Patient and method: Prospective study conducted in Baghdad Teaching Hospital and Dijlah private hospital from October 2009 to October 2013. Thirty patients with idiopathic thrombocytopenic purpura(ITP) were included and had laparoscopic splenectomy . The adapted procedure was stapleless laproscopic splenectomy, without clips using vessels sealing device only. Result: A total of 30 patients were recruited. The mean of their ages was 25.2 years. Eleven of them were males and 19 were females. The mean operative time was 84.3 min. The mean estimated blood loss was 105 ml. Twenty seven spleens were extracted through small Pfannenstiel incision and 3 spleens were retrieved by retrieval bag. No conversion had occurred; the mean hospital stay was 2.3 days. Neither bleeding nor any other serious complication related to this technique were observed, only one patient complicated by collection which was treated by aspiration under ultrasound guide. No mortalities were recorded. Conclusion: Laparoscopic splenectomy of normal size and mildly enlarged spleen with use of vessels sealing device without staple or clips is safe and effective.